2019
DOI: 10.3389/fnhum.2018.00529
|View full text |Cite
|
Sign up to set email alerts
|

Can a Subjective Questionnaire Be Used as Brain-Computer Interface Performance Predictor?

Abstract: Predicting a subject's ability to use a Brain Computer Interface (BCI) is one of the major issues in the BCI domain. Relevant applications of forecasting BCI performance include the ability to adapt the BCI to the needs and expectations of the user, assessing the efficiency of BCI use in stroke rehabilitation, and finally, homogenizing a research population. A limited number of recent studies have proposed the use of subjective questionnaires, such as the Motor Imagery Questionnaire Revised-Second Edition (MIQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 51 publications
0
42
3
Order By: Relevance
“…For the present study, we, cannot follow up on this possibility, given that we did not include an MI ability or severity questionnaire. It should, however, be noted that former studies found no (Rimbert et al, 2019) or rather moderate (Vuckovic and Osuagwu, 2013;Marchesotti et al, 2016) relations between subjective MI ability measures and BCI literacy.…”
Section: Study Limitationsmentioning
confidence: 70%
“…For the present study, we, cannot follow up on this possibility, given that we did not include an MI ability or severity questionnaire. It should, however, be noted that former studies found no (Rimbert et al, 2019) or rather moderate (Vuckovic and Osuagwu, 2013;Marchesotti et al, 2016) relations between subjective MI ability measures and BCI literacy.…”
Section: Study Limitationsmentioning
confidence: 70%
“…Indeed, especially in studies involving human beings, users and experimenters can have a notable influence on the results. As an example, Rimbert et al [29] have conducted an experiment whose goal was to confirm the effectiveness of the use of subjective questionnaires, such as the Motor Imagery Questionnaire Revised-Second Edition (MIQ-RS), to estimate the performance of a Motor Imagery (MI)-based BMI. Predicting a subject's ability to use a BMI is one of the major issues in the BMI domain.…”
Section: Examples Of Useful Negative Results In Bmimentioning
confidence: 99%
“…A lack of association between objective and subjective quality of MI is also reported in recent Brain‐Computer Interface studies focused on MI. For example, Rimbert, Gayraud, Bougrain, Clerc, and Fleck (2018) showed no significant correlation between MI performance (measured by taking into account the average classification accuracy on EEG data between right‐hand MI and a rest period) and the scores obtained at the Motor Imagery Questionnaire Revised‐Second Edition (Rimbert et al, 2018).…”
Section: Discussionmentioning
confidence: 99%